Prenatal Progestin Exposure Is Associated With Autism Spectrum Disorders - Li, Ling; Li, Min; Lu, Jianping; Ge, Xiaohu; Xie, Weiguo; Wang, Zichen; Li, Xiaoling; Li, Chao; Wang, Xiaoyan; Han, Yan; Wang, Yifei; Zhong, Liyan; et al. (Frontiers in Psychiatry, 2018)
We have previously reported that prenatal progestin exposure induces autism-like behavior in offspring through ERβ (estrogen receptor β) suppression in the brain, indicating that progestin may induce autism spectrum disorders (ASD). In this study, we aim to investigate whether prenatal progestin exposure is associated with ASD. A population-based case-control epidemiology study was conducted in Hainan province of China. The ASD children were first screened with the Autism Behavior Checklist (ABC) questionnaire, and then diagnosed by clinical professionals using the ASD diagnosis criteria found in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V). Eventually, 235 cases were identified as ASD from 37863 children aged 0–6 years old, and 682 matched control subjects with typically developing children were selected for the analysis of potential impact factors on ASD prevalence using multivariate logistic regression. Our data show that the ASD prevalence rate in Hainan was 0.62% with a boy:girl ratio of 5.4:1. Interestingly, we found that the following factors were strongly associated with ASD prevalence: use of progestin to prevent threatened abortion, use of progestin contraceptives at the time of conception, and prenatal consumption of progestin-contaminated seafood during the first trimester of pregnancy. All the above factors were directly or indirectly involved with prenatal progestin exposure. Additionally, we conducted in vivo experiments in rats to further confirm our findings. Either endogenous (progesterone) or synthetic progestin (norethindrone)-treated seafood zebrafish were used to feed pregnant dams, and the subsequent offspring showed autism-like behavior, which further demonstrated that prenatal progestin exposure may induce ASD. We conclude that prenatal progestin exposure may be associated with ASD development.